Estudo da viabilidade do cladócero tropical Macrothrix elegans Sars, 1901 (Cladocera, Macrothricidae) como organismo-teste em ensaios ecotoxicológicos. - Pinho, Salomão José Cohin (2007)
The current study investigates the suitability of a tropical cladoceran species, Macrothrix elegans Sars (1901) for toxicity testing in ecotoxicological tests at 250C involving two reference substances, cadmium chloride (CdCl2) both in natural and artificial media, and potassium chloride (KCl) in natural medium. The work provides a comparison among other cladoceran species from tropical and temperate environments, and discusses the potential of M. elegans as a bioindicator of stress in tropical waters. An experiment on the animal’s life-span has been included to assess its reproductive potential. On average, at 250C, M. elegans lives 38.2 ± 4.4 days and each female produces 211.8±30.4 neonates. The criterion of toxicity adopted in the bioassays was mortality/immobility using neonates up to 24-h old. The CdCl2 48-h EC50 mean values and their confidence intervals were 0.035 mg.l-1 [0.020-0.050 mg.l-1] in natural medium, and 0.018 mg.l-1 [0.012-0.024 mg.l-1] in the artificial medium. The KCl 48-h EC50 mean value (natural medium only) was 749.08 mg.l-1 [625.32-872.76 mg.l-1]. The work demonstrates the great potential of M. elegans as a test organism in ecotoxicological tests involving these substances in tropical freshwater ecosystems.